2013
DOI: 10.3109/13880209.2012.749922
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor activities of extracts from selected desert plants against HepG2 human hepatocellular carcinoma cells

Abstract: Context: Phytochemicals are produced by desert plants to protect themselves against stressful environments. They have been shown to be useful in preventing and fighting adverse pathophysiological conditions and complex diseases, including cancer. Although many desert plants have been investigated for their antitumor properties, a large number of them still remain to be explored for possible therapeutic applications in oncologic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 34 publications
1
25
0
Order By: Relevance
“…A recent study reported cytotoxic effect of an aqueous extract of A. fragrantissima against HepG2 human hepatocellular carcinoma cells [33]. The MTT assay was used as a relative measure of cell viability to study the anti-proliferative activity of the aqueous and hydro-alcoholic A. fragrantissima extracts against the MCF-7 cells.…”
Section: Cytotoxicity Effectmentioning
confidence: 99%
“…A recent study reported cytotoxic effect of an aqueous extract of A. fragrantissima against HepG2 human hepatocellular carcinoma cells [33]. The MTT assay was used as a relative measure of cell viability to study the anti-proliferative activity of the aqueous and hydro-alcoholic A. fragrantissima extracts against the MCF-7 cells.…”
Section: Cytotoxicity Effectmentioning
confidence: 99%
“…Different species of Phlomis have been used in the treatment of diabetes, stomach ulcer, hemorrhoids and inflammations (26). In addition, the antibacterial, anticancer, and antioxidant activities have been reported for them (27,28). The main compounds of the essential oil of P. olivieri, obtained from its leaves, were Momtaz HE et al normal-octane (28.77%), camphor (13.32%), 1,8-cineol (12.24%), α-pinene (7.8%), and germacrene D (6.57%) (29).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study described cytotoxic effect of A. fragrantissima aqueous extract on HepG2 human hepatocellular carcinoma cells (Thoppil et al, 2013).…”
Section: Resultsmentioning
confidence: 99%